PENGELOLAAN PERIKANAN KARANG DI TAMAN NASIONAL WAKATOBI: PERSPEKTIF AKTOR DAN AGEN - Mercy - Patanda; Sugeng Hari Wisudo; Daniel Rudolf Monintja; Budy - Wiryawan (Bogor Agricultural University, 2018)
Stakeholders, who are agents and actors in this matter play an important role in the management of reef fisheries in Wakatobi National Park. This study aims to identify the agents and actors in Wakatobi Regency and to identify similarities and differences of the perception between agents and actors in the management of conservation areas. The method used isÂ Principal Component Analysis (PCA). The result showed that there was a similar perception between agent and actor in which that the conservation gives benefit for the society in Wakatobi and the lack of regulation in Wakatobi Regency. Different perceptions between actors and agents occurred due to fishermen intention to fully utilize the resources for their welfare while the government intents to limit the fishing area in order to preserve the natural resources and the environment. Therefore, management related to theÂ regulation on legal-size of fish and the effectiveness of marine protected areas are needed. Keywords: Stakeholders, Coral Reef, Conservation, WakatobiABSTRAKPemangkuÂ kepentingan sangat berperan penting dalam pengelolaan perikanan karang di Taman Nasional Kabupaten Wakatobi. Tujuan penelitian adalah mengidentifikasi agen dan aktor yang berada di Kabupaten Wakatobi serta melihat persamaan dan perbedaan persepsi antara agen dengan aktor dalam pengelolaan kawasan konservasi. Penelitian ini menggunakan analisis Principal Component Analysis (PCA). Hasil kajian menunjukkan adanya persamaan persepsi antara agen dan aktor yaitu konservasi memberikan manfaat bagi masyarakat yang ada di Wakatobi dan masih kurangnya peraturan di Kabupaten Wakatobi. Perbedaan persepsi pada aktor dan agen karena nelayan ingin memanfaatkan perairan Taman nasional Wakatobi semaksimal mungkin untuk kesejahteraan nelayan sedangkan pemerintah membatasi wilayah penangkapan dalam rangka menjaga sumber daya alam dan lingkungannya sehingga perlu tindakan pengelolaan yaitu penentuan ukuran ikan yang tertangkap dan pengefektifan daerah perlindungan laut.Kata kunci: Pemangku Kepentingan, Perikanan Karang, Konservasi, Wakatobi